Single‐Product Faradaic Efficiency for Electrocatalytic of CO2 to CO at Current Density Larger than 1.2 A cm−2 in Neutral Aqueous Solution by a Single‐Atom Nanozyme - Huang, Jia‐Run; Qiu, Xiao‐Feng; Zhao, Zhen‐Hua; Zhu, Hao‐Lin; Liu, Yan‐Chen; Shi, Wen; Liao, Pei‐Qin; Chen, Xiao‐Ming (Angewandte Chemie International Edition, 2022)
Electroreduction of CO2 to CO is a promising approach for the cycling use of CO2, while it still suffers from impractical current density and durability. Here we report a single‐atom nanozyme (Ni−N5−C) that achieves industrial‐scale performance for CO2‐to‐CO conversion with a Faradaic efficiency (FE) exceeded 97 % over −0.8–−2.4 V vs. RHE. The current density at −2.4 V vs. RHE reached a maximum of 1.23 A cm−2 (turnover frequency of 69.7 s−1) with an FE of 99.6 %. No obvious degradation was observed over 100 hours of continuous operation. Compared with the planar Ni−N4 site, the square‐pyramidal Ni−N5 site has an increase and a decrease in the dz2 ${{{\rm d}}_{{z}^{2}}}$ and dxz/yz orbital energy levels, respectively, as revealed by density functional theory calculations. Thus, the Ni−N5 catalytic site is more superior to activate CO2 molecule and reduce the energy barriers as well as promote the CO desorption, thus boosting the kinetic activation process and catalytic activity. In neutral aqueous solution, a single‐atom nanozyme Ni−N5−C with enzyme‐like catalytic active sites exhibited ultra‐high current density of 1.2 A cm−2 and durability of 100 h for electroreduction of CO2 to CO.